Islamic Jurisprudence on Women Reproductive Health (Indonesian Review) - Qibtiyah, Alimatul; Andeska, Wika; Salsabila, Azka (Indonesian Journal of Islamic Economic Law, 2025)
This paper explores the role of Islamic jurisprudence (fiqh) in addressing women's reproductive health issues in Indonesia, particularly in emergency contexts where rising sexual violence is prevalent. Islamic jurisprudence, as part of the turats (heritage), provides a moral and legal framework that can bridge traditional Islamic principles with contemporary reproductive health challenges. The formulation of women's reproductive health jurisprudence in Islam must be grounded in the fundamental values of benefit (maṣlaḥah), justice, and freedom, which are in alignment with the principles of maqāṣid al-sharī’ah, particularly hifẓ al-nafs (protecting the soul) and hifẓ al-nasl (protecting offspring). Women's reproductive health encompasses not only the prevention of disease but also the safeguarding of reproductive rights in accordance with Islamic values, including the right of women to make medical decisions regarding their health. Consequently, access to safe and quality reproductive health services must be regarded as harmful practices such as child marriage, female genital mutilation/cutting (FGM/C), and restrictions on contraception that endanger the mother's health. It is imperative to recognize that all practices detrimental to women's reproductive health are considered haram, as they contradict the principle of benefit. To address this critical issue, there is a necessity to reformulate fiqh to align more closely with the contemporary needs of women. This reformulation must affirm women's rights to their reproductive health and ensure the development of inclusive health policies based on maqāṣid al-sharī’ah. These policies must protect women's health from harmful and discriminatory practices. This paper underscores the pressing need to integrate Islamic legal principles to safeguard women's reproductive rights, aligning Islamic jurisprudence with contemporary reproductive health needs, particularly during times of crisis, to achieve a more comprehensive approach to safeguarding women's health and dignity